2014
DOI: 10.1517/13543784.2014.911839
|View full text |Cite
|
Sign up to set email alerts
|

Investigational FMS-like tyrosine kinase 3 inhibitors in treatment of acute myeloid leukemia

Abstract: Introduction Outcomes for the majority of patients with Acute Myeloid Leukemia (AML) remain poor. Over the past decade, significant progress has been made in the understanding of the cytogenetic and molecular determinants of AML pathogenesis. One such advance is the identification of recurring mutations in the FMS-like tyrosine kinase 3 gene(FLT3). Currently, this marker, which appears in approximately one third of all AML patients, signifies a poorer prognosis, but also identifies an important target for ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 89 publications
(105 reference statements)
0
19
0
Order By: Relevance
“…While many Flt3 inhibitors have been tested in clinical trials, none has produced durable responses as monotherapy for AML. One important example is quizartinib (also known as AC220), a very potent and selective Flt3 inhibitor that was among the first to show efficacy as a single agent against Flt3-ITD + AML 5,31 . Quizartinib often induces rapid remission in Flt3-ITD + AML, but acquired drug resistance, commonly in the form of Flt3 kinase domain mutations, has limited its effectiveness 4,5,3234 .…”
Section: Resultsmentioning
confidence: 99%
“…While many Flt3 inhibitors have been tested in clinical trials, none has produced durable responses as monotherapy for AML. One important example is quizartinib (also known as AC220), a very potent and selective Flt3 inhibitor that was among the first to show efficacy as a single agent against Flt3-ITD + AML 5,31 . Quizartinib often induces rapid remission in Flt3-ITD + AML, but acquired drug resistance, commonly in the form of Flt3 kinase domain mutations, has limited its effectiveness 4,5,3234 .…”
Section: Resultsmentioning
confidence: 99%
“…Dohner and colleagues 49 , recently reported that mutant NPM1 confers a favorable prognosis in AML AYA patients, particularly when in the absence of any concomitant FLT3 -ITD 21,49 . Since FLT3 and other molecular makers have only been widely available and part of the AML diagnostic workup over the most recent time period studied (2000-2009) 50 , our analysis focused on cytogenetic subgrouping, as this was available on the majority of patients included in the study period. Future studies will further define the impact of molecular characterization in the AYA population.…”
Section: Discussionmentioning
confidence: 99%
“…Several FLT3-ITD inhibitors (quizaritinib, sorafenib, midostaurin) have shown encouraging results in combination with chemotherapy[5,160172]. These tyrosine kinase inhibitors competitively inhibit ATP-binding sites on FLT3 kinase domain (KD).…”
Section: Treatment Of Amlmentioning
confidence: 99%
“…First- and second-generation FLT3-inhibitors (sorafenib, midastaurin, quizartinib, crenolanib, and ASP2215), small-molecule inhibitors of BET and DOT1L histone methyltransferase targeting MLL translocations, SGN-33a and GO targeting CD33 in patients with CBF-AML and APL, IDH1 and IDH2 inhibitors for patients with IDH mutations (AG-120, ABT-199, AG-221), RAS and MEK inhibitors (trametinib and MEK162), and other targets and targeted therapies are currently under investigation, giving hope for better therapies for adult patients with AML[49,160,205,219–221]. …”
Section: Treatment Of Amlmentioning
confidence: 99%